Jail Inmates in 2019 - statistical tables - Zeng, Zhen (Prison and Jail Inmates at Midyear, Jail Inmates, 2021)
This report is the 33rd in a series that began in 1982. It provides statistics based on BJS's Annual Survey of Jails and Census of Jails. It describes the number of inmates held in local jails, jail incarceration rates, demographic characteristics of jail inmates, the number of admissions to jail, jail capacity, inmate turnover rates, and staff employed in local jails.